2005
DOI: 10.3171/ped.2005.103.6.0549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trichostatin A, a histone deacetylase inhibitor, on glioma proliferation in vitro by inducing cell cycle arrest and apoptosis

Abstract: The TSA caused inhibition of glioma cell growth by both cell cycle arrest and apoptosis. Cell cycle arrest was associated with an increase in p21WAF1 expression and a decrease in phosphorylated Rb. Apoptosis was mediated at least partly through the activation of caspase-3. Because of the differential effects in glioma cells compared with nonneoplastic cells, TSA may provide a novel strategy for achieving tumor growth inhibition and cytotoxicity. Further investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 30 publications
4
45
0
2
Order By: Relevance
“…TSA treatment caused significant cell death at 48 h, and no cell damage was found in 5-Aza-dC treated cells. Similar results were reported previously in the treatment of cancer cells with epigenetic reagents (28,29).…”
Section: Heparanase Expression Is Restored By Epigenetic Modificationssupporting
confidence: 80%
“…TSA treatment caused significant cell death at 48 h, and no cell damage was found in 5-Aza-dC treated cells. Similar results were reported previously in the treatment of cancer cells with epigenetic reagents (28,29).…”
Section: Heparanase Expression Is Restored By Epigenetic Modificationssupporting
confidence: 80%
“…5B). Because the CDK inhibitor p21WAF1 was increased in glioma cells by TSA (Wetzel et al, 2005), we tested the time course of SAHAmediated p21 expression. Cells were exposed to varying concentrations of SAHA; lysates were prepared and probed with antibodies recognizing p21 Cip/Waf.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Cip/Waf expression and decreased phosphorylated retinoblastoma protein (Wetzel et al, 2005). Suberoylanalide hydroxamic acid (SAHA, vorinostat), an inhibitor of several members of the HDAC protein family (Finnin et al, 1999), has also been observed to have antiglioma activity in preclinical studies, causing GBM cells to accumulate in the G 2 -M phase of the cell cycle, with increased expression of p21WAF1 and p27KIP1, decreased levels of cyclin-dependent kinase (CDK) 2, CDK4, cyclin D1, and cyclin D2 (Yin et al, 2007), and inhibition of GBM growth in orthotopic models.…”
mentioning
confidence: 99%
“…A ação da tricostatina A foi testada in vitro em vários tipos de células tumorais, demonstrando seu efeito inibitório no ciclo celular e apoptose (MEDINA et al, 1997;VIGUSHIN et al, 2001;YEE et al, 2004;WETZEL et al, 2005;MUKHOPADHYAY et al, 2006) e invasão celular (WU; STARZINSKI-POWITZ;…”
Section: Zinco-independentes Nicotinamida-adenina Dinucleotídeo Depeunclassified
“…Quando associado a 5-aza-2-deoxicitidina (AZA) (CANTOR et al, 2007), ácido retinóico (TOUMA et al, 2005) HENDERSON et al, 2003;WETZEL et al, 2005;MUKHOPADHYAY et al, 2006;STARZINSKI-POWITZ;HONG et al, 2009 aumento na fração sub-G1 do ciclo celular. Interessantemente, o tratamento com 1000 µg/ml de RBPP nas células produziu um aumento na proporção de células marcadas na fase S dos tempos de 48 e 72h, e diminuição concomitante na proporção de células em G1 e G2.…”
Section: Estudosunclassified